Unifying Knowledge, Reasoning, and Hierarchy for Classifying Harmful Content - Raden Budiarto; I Gede Maha Putra (Ikatan Ahli Informatika Indonesia (IAII), 2026)
The spread of negative, engagement-driven content online causes significant societal harm, requiring advanced automated moderation tools. However, current classification systems often treat harmful content subtypes as independent,